2015
DOI: 10.1109/tap.2015.2414948
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Flush-Mounted Surface Wave Antenna of Very Low Profile

Abstract: This paper presents the design of a compact and wideband surface wave antenna that exhibits very low profile and can be flush-mounted on a conformal platform. The proposed antenna comprises a tapered grounded ceramic slab, a unidirectional surface wave launcher, and a tapered impedance transition. The ceramic slab is smoothly tapered to transform the guided surface wave into radiated space wave over a wide frequency range. The surface wave launcher employs a probe-fed parallel plate waveguide with a modified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 26 publications
1
62
0
Order By: Relevance
“…The solution of suppressing surface waves on grounded anisotropic slab was explored in [17]. Furthermore, investigations were also focused on the radiation conditions of surface wave on grounded dielectric slabs, which have been employed for designing wideband, low-profile, as well as high gain antennas [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution of suppressing surface waves on grounded anisotropic slab was explored in [17]. Furthermore, investigations were also focused on the radiation conditions of surface wave on grounded dielectric slabs, which have been employed for designing wideband, low-profile, as well as high gain antennas [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…(i) It is revealed that no pure TM or TE mode exists on the grounded infinitely large slab if the field is non-uniformly distributed along the direction orthogonal to the propagation direction; (ii) Closed-form analytical expressions are derived to theoretically study the characteristics of quasi-TM and quasi-TE surface modes on the finite-width grounded anisotropic grounded slab. It is found that surface waves propagate away from the longitudinal direction of the finite-width slab with some certain angle, and the angle decreases as the slab width increases; (iii) Different from the existing analyses of surface waves whose fields distribute uniformly along the transverse direction of the infinitely large slab, our method takes into account the variations of the fields distributed on the transverse direction of the grounded anisotropic slab, which has a more practical relevance and can provide a more accurate solution for engineering applications such as designing wideband and high gain antennas based on grounded dielectric slabs [9,[18][19][20]. It is worth mentioning that our method is also suitable for grounded isotropic dielectric slab.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, different techniques have been utilized to propose wideband flush-mounted antennas with low profile and end-fire radiation [2]- [16]. Microstrip Yagi array antennas have been first introduced in [2] and further developed in [3]- [6] with the advantages of end-fire radiation, low profile and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, the antenna feeding geometry in [13] is complicated and the impedance bandwidth is only matched to VSWR < 2.5 instead of 2. Surface wave antennas have been studied in [14]- [16]. In [16], a surface wave antenna with a very low profile of 0.061 λL has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A three-element patch array based ESPAR is proposed in [17], which achieves continuous scanning range of -15 o to 15 o in the elevation plane. Nevertheless, end-fire beams are preferable in some applications such as unmanned aerial vehicle (UAV) and wireless communications for azimuth signal coverage [18].…”
Section: Introductionmentioning
confidence: 99%